Integrating Data Analytics into Traditional Media: Opportunities and Strategic Advantages - Веньхао Чжен; Вікторія Опанасенко (Український інформаційний простір)
As traditional media transforms and adapts to the digitalisation epoch, data analysis technology becomes a critical tool for enhancing competitiveness and ensuring relevance in a rapidly changing conditions. Many news organisations are increasingly adopting data analytics strategies in order to improve the production of personalised news content and value-based advertising for more precise audience targeting. It allows them to deliver content that resonates with their viewers. To achieve this, media conducts in-depth analysis of users’ behaviour, preferences and engagement patterns, resulting in a clear understanding of their audience and, consequently, more informed decision-making. However, the way to fully integrating data analytics into traditional media is not without significant challenges. Media organisations frequently face obstacles such as inadequate technical infrastructure, limited access to skilled data professionals, and the necessity in specialised training the existing staff in order to handle data effectively. Moreover, the use of personal data raises concerns in terms of privacy and ethical standards, which necessitates a careful balancing act between leveraging data for analysing and maintaining the users’ trust. Furthermore, issues related to data quality, including inconsistencies, incomplete resources and management of massive data volumes, pose additional hurdles which can complicate the accuracy and effectiveness of analytics results.